Giving Professional Presentations in the Behavioral Sciences and Related Fields : a Practical Guide for Novice, the Nervous and the Nonchalant. - Platow, Michael (Taylor and Francis, 2012)
Gives concrete advice about designing, delivering, and defending presentations, and is written specifically for students and professionals who have little or no experience of giving presentations.